Bronchial-arterial-circulation-sparing Lung Preservation: A New Organ Protection Approach for Lung Transplantation. Issue 3 (March 2020) - Tane, Shinya; Noda, Kentaro; Toyoda, Yoshiya; Shigemura, Norihisa
Abstract : Background: Compromised microvasculature resulting from disrupted bronchial arterial circulation appears to trigger chronic lung allograft dysfunction. Maintaining the microvasculature throughout the transplant process could improve the long-term health of transplanted lungs. We recently developed a bronchial-arterial-circulation-sparing (BACS) lung preservation approach and tested whether this approach would decrease microvascular damage and improve allograft function. Methods: The lungs of Lewis rats were procured using either the BACS approach, where the bronchial and pulmonary arteries were synchronously perfused; a conventional approach, where only the pulmonary artery was perfused; or a conventional approach with a prostaglandin flush. After 4 hours of cold ischemia, physiologic function and vascular tone of the grafts were evaluated during ex vivo lung perfusion (EVLP), and microvasculature damage was assessed using 2-photon microscopy analysis. Lung function was compared after transplant among the groups. Results: After 4 hours of cold ischemia, the BACS group exhibited significantly higher adenosine triphosphate levels and lower expression of phosphorylated myosin light chain, which is essential for vascular smooth muscle contraction. On EVLP, the BACS and prostaglandin groups showed lower pulmonary vascular resistance and less arterial stiffness. BACS attenuated microvasculature damage in the lung grafts when compared with conventional preservation. After transplantation, the lungs preserved with the BACS approach exhibited significantly better graft function and lower expression of phosphorylated myosin light chain. Conclusions: Our data suggest that BACS lung preservation protects the dual circulation inherent to the lungs, facilitating robust microvasculature in lung grafts after transplantation, leading to better posttransplant outcomes.